KIF18B promotes hepatocellular carcinoma progression through activating Wnt/β‐catenin‐signaling pathway. Issue 10 (13th February 2020) - Yang, Bin; Wang, Shengzhi; Xie, Hui; Wang, Chunping; Gao, Xudong; Rong, Yihui; Liu, Zhenwen; Lu, Yinying
Abstract: This study aimed to investigate the functional roles of kinesin family member 18B ( KIF18B ) in hepatocellular carcinoma (HCC) development, as well as the related molecular mechanisms. Tissue specimens were collected from 105 patients with HCC, and the messenger RNA (mRNA) and protein levels of KIF18B were detected using quantitative real‐time polymerase chain reaction and immunohistochemistry assays, respectively. The χ 2 test was performed to estimate the association of KIF18B with clinical characteristics of patients with HCC. Effects of KIF18B expression on biological behaviors of HCC cells were detected by clone formation, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide, and transwell assays. The expression patterns of proteins were investigated using Western blot analysis. HCC tissues and cell lines showed significant upregulation of KIF18B at both mRNA and protein levels ( p  > .05, for all). Furthermore, the elevated KIF18B expression was positively correlated with the tumor‐node‐metastasis stage ( p  = .015) and lymph node metastasis ( p  = .007). Knockdown of KIF18B might suppress HCC cell clone formation, proliferation, migration, and invasion in vitro. Besides, the activity of Wnt/β‐catenin pathway was also significantly inhibited after the  KIF18B knockdown. However, the antitumor actions caused by KIF18B knockdown might be reversed by lithium chloride treatment, which was the inducer of Wnt/β‐catenin‐signaling pathway. KIF18B may serve as an oncogene in HCC through enhancing the activity of Wnt/β‐catenin pathway. Abstract : This study aimed to investigate the functional roles of kinesin family member 18B (KIF18B) in hepatocellular carcinoma (HCC) development, as well as the related molecular mechanisms.